Spider Construction Readiness Assessment: Studi Kesiapan Proyek Pembangunan Gedung Asrama MTsN 6 Sleman - Muhammad Atana Nur Fauzi; Agus Priyanto (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2021)
Abstracts. Delays in construction projects are caused by incorrectly estimating the time needed to complete the project in the planning stage, inaccurate management, problems with materials, labor, equipment, finance, and an unfavorable environment that hinders project implementation. Project delays for the contractor will incur time and cost losses. For the Owner, delays in completing project work will cause losses to the operational time of the project results. The case study reviewed was the construction of the MTsN 6 dormitory building located in Rogoyudan, Sinduadi, Mlati District, Sleman Regency, Yogyakarta. The idea to minimize delays in development projects is to create a readiness assessment system in the form of a spider construction readiness assessment, namely an assessment of aspects of administrative documents, site location, funds and materials, implementation methods, quality and quantity of human resources, project design, and external factors. The preparation of an assessment is based on 45 factors that can hinder the development of a project. The results of the assessment show that the total score obtained from all aspects is 52 out of 70. This means that construction project readiness has a figure of 74.29%. Aspects that need to be improved in performance are aspects of design readiness, aspects of method readiness, and aspects of external studies. The final results of the study indicate that the Spider construction readiness assessment can be used as a way to mprove work efficiency at the pre-construction stage.Â Keywords: project delays, project readiness, spider construction readiness assessment